2012
DOI: 10.1016/j.jacc.2012.03.070
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of an Implantable Cardioverter-Defibrillator in Patients With Vasospastic Angina and Lethal Ventricular Arrhythmia

Abstract: Patients with VSA and lethal ventricular arrhythmia are a population at high risk for recurrence of cardiopulmonary arrest, and there is no reliable indicator for predicting recurrence of ventricular arrhythmia. Insertion of an ICD with medication for VSA is appropriate for this high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
91
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 21 publications
0
91
0
2
Order By: Relevance
“…39 Furthermore, in an observational study of 23 patients who had vasospasm with ventricular arrhythmia, at a median follow-up of 2.1 years, 5 patients had a cardiac arrest (4 with ventricular fibrillation and 1 with pulseless electric activity). 40 Considering the morbidity associated with long-term intracardiac devices, particularly in this patient population, which tends to be younger, alternatives, such as a subcutaneous ICD or wearable cardioverter-defibrillator, may be considered in the future. For example, a recent communication describes the use of a wearable cardioverter-defibrillator in patients with a high risk of sudden cardiac death, including one with coronary artery vasospasm.…”
Section: February 23 2016mentioning
confidence: 99%
“…39 Furthermore, in an observational study of 23 patients who had vasospasm with ventricular arrhythmia, at a median follow-up of 2.1 years, 5 patients had a cardiac arrest (4 with ventricular fibrillation and 1 with pulseless electric activity). 40 Considering the morbidity associated with long-term intracardiac devices, particularly in this patient population, which tends to be younger, alternatives, such as a subcutaneous ICD or wearable cardioverter-defibrillator, may be considered in the future. For example, a recent communication describes the use of a wearable cardioverter-defibrillator in patients with a high risk of sudden cardiac death, including one with coronary artery vasospasm.…”
Section: February 23 2016mentioning
confidence: 99%
“…The nationwide multicenter study conducted by the Japanese Coronary Spasm Association found that VSA patients who survived OHCA are particularly a high-risk population, even in the current era with long-acting calcium channel blockades (Takagi et al 2011). Although a recent study with a small number of patients reported that ICD therapy combined with medication is appropriate for this high-risk VSA population (Matsue et al 2012), further studies are needed to determine whether ICD therapy improves the long-term prognosis of VSA patients who survived OHCA.…”
Section: Sudden Cardiac Death In Variant Anginamentioning
confidence: 99%
“…Yusuke Takagi, MD, PhD 9 Meisel et al 10 Meune et al 11 Takagi et al 12 Takagi et al 13 Matsue et al 14 Kobayashi et al 15 Subjects, n 5 …”
Section: Coronary Vasospasm As An Underlying Etiology Of Out-of-hospimentioning
confidence: 99%